Analytical Solution For Buckling Of Laminated Conical Shells - Alazzawy, Wedad I. (Nahrain University College of Engineering Journal, 2009)
Buckling analysis of laminated conical shells under axial compressive load are investigated analytically using high order and Love ,s shell theories. Power series are used to solve the developed equations of motion for conical shells with different semi vertex angles, length- to radius ratio, number of layers and boundary conditions. The validity of the presented procedure is confirmed.